LEVERAGE MEDIATING DETERMINANT TAX AVOIDANCE IN INDUSTRIAL SECTOR COMPANIES INDONESIA - Amanda Safa Sabitha; Awalia Az Zahra; Vina Amaliya; Hakim, Mohamad Zulman; Hesty Erviani Zulaecha; Eko Sudarmanto (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the effect of Profitability, Company Size, and Executive Character on Tax Avoidance with Leverage as an intervening variable. This study was conducted on industrial companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2023. The study's sample, consisting of 67 industrial sector companies listed on the IDX, was selected using purposive sampling. Based on specific criteria, 48 data points and 27 industrial-related firms were chosen as representatives for the analysis. The study used the Descriptive Statistical Analysis method with samples obtained from the financial statements of companies listed on the IDX during that period. The results of this study prove that simultaneously show that Profitability, Company Size, Executive Character has an effect on Tax Avoidance. Profitability has an effect on Leverage. Company Size and Executive Character do not affect Leverage. Profitability, Company Size and Leverage do not affect Tax Avoidance. Executive Character affects Tax Avoidance. Leverage is unable to intervene in the relationship between Profitability, Company Size and Executive Character on Tax Avoidance.